Animal Health Risk assessment of multiple chemicals in essential oils for farm animals. Issue 1 (30th January 2020) - ,; Dorne, Jean Lou CM; Manini, Paola; Hogstrand, Christer
Abstract : This technical report implements the EFSA MIXTOX guidance document for animal health risk assessment of combined exposure to multiple chemicals in essential oilsusing whole mixture and component‐based approaches (WMA and CBA).The harmonised step wise approaches from the MIXTOX guidance are applied to the problem formulation, exposure assessment, hazard assessment and risk characterisation using conservative scenarios, available data and tools. Options for the refinement of the CBA are proposed for the exposure assessment and hazard assessment (toxicity and toxicokinetic data and models) steps as well as for the application of risk characterisation methods.For exposure assessment, exposure metrics are derived for the whole mixture or for each component of the assessment groupusing the maximum proposed use levels of the essential oil in feedcombined with the feed consumption patterns corrected for body weight for each farm animal species. For hazard assessment, combined chronic toxicity on a species‐specific basis requires data collection of reference points from chronic tolerance studies in each farm species or (sub)‐chronic toxicity studies on test species. For the WMA, the chronic toxicity of the whole mixture is used and divided by uncertainty factors.For the component‐based approach, the chronic toxicity for each substance in each assessment group is collected. For risk characterisation using WMA and CBA, a margin of exposure approach and a combined margin of exposure approach are applied respectively.Options for refining the approachesfor the component‐based approach are proposedincluding the use ofspecific toxic effectsfor the grouping of chemicals as well as the use of toxicokinetic data and generic physiologically‐based kinetic models for farm animal species.